2021
DOI: 10.1093/bib/bbab202
|View full text |Cite
|
Sign up to set email alerts
|

DITHER: an algorithm for Defining IntraTumor Heterogeneity based on EntRopy

Abstract: Intratumor heterogeneity (ITH) is associated with tumor development, prognosis, immune evasion and therapeutic effects. We proposed the Defining ITH based on EntRopy (DITHER) algorithm for evaluating ITH. We first evaluated the entropies of somatic mutation profiles and copy number alteration (CNA) profiles in a tumor, respectively, and defined their average as the ITH level for the tumor. Using DITHER, we analyzed 33 cancer types from The Cancer Genome Atlas (TCGA) program. We demonstrated that the ITH define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 23 publications
2
19
0
Order By: Relevance
“…This is consistent with our results that Immunity-H had higher TMB and lower levels of CNAs than Immunity-L. In addition, the markedly lower ITH in Immunity-H vs. Immunity-L supports the notion that ITH can contribute to tumor immune evasion (23,47).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with our results that Immunity-H had higher TMB and lower levels of CNAs than Immunity-L. In addition, the markedly lower ITH in Immunity-H vs. Immunity-L supports the notion that ITH can contribute to tumor immune evasion (23,47).…”
Section: Discussionsupporting
confidence: 92%
“…The G-score represents the amplitude of the SCNA and the frequency of its occurrence across a class of samples ( 22 ). We utilized the DITHER algorithm ( 23 ) to score ITH, which measures ITH based on both somatic mutation and SCNA profiles. The ESTIMATE algorithm ( 24 ) was used to calculate immune scores, stromal scores, and tumor purity for bulk tumors, which represent immune infiltration levels, stromal contents, and proportions of tumor cells in bulk tumors.…”
Section: Methodsmentioning
confidence: 99%
“…Because tumor immune signatures, stemness, and ITH are associated with clinical outcomes in cancer (18,23,24) and had significantly different scores between the HPV+ cervical cancer subtypes, the survival difference between the subtypes could be impacted by these confounding variables. To explore the possibility, we performed multivariate (immune score, stemness score, ITH score, and subtype) survival analysis with the multivariate Cox proportional hazards model.…”
Section: Subtyping Of Hpv+ Cervical Cancersmentioning
confidence: 99%
“…The G-score represents the amplitude of the CNA and the frequency of its occurrence across a group of samples [22] . We used the DITHER algorithm [6] to evaluate ITH levels, which scores ITH based on the entropies of somatic mutation profiles and SCNA profiles in the tumor.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, with the advances in sequencing, genomics, and computational technologies, mounting large-scale multi-omics data for cancer have emerged, such as the Cancer Genome Atlas (TCGA, https://cancergenome.nih.gov ). These multi-omics data provide valuable resource for exploring cancer features, e.g., tumor stemness [1] , [4] , ITH [5] , [6] , and tumor immunity [7] . In fact, multi-omics data analyses have shown that tumor stemness is associated with dedifferentiated oncogenic phenotype, metastasis, ITH, and immunosuppression across various cancers [1] , [4] .…”
Section: Introductionmentioning
confidence: 99%